(untitled) (Ágora de Heterodoxias, 2025)
Venezuela is facing a humanitarian crisis that has significantly exacerbated poverty and inequality. This essay examines the impact of the crisis on Venezuela’s progress towards Sustainable Development Goal 1: No poverty. Using data from the National Survey of Living Conditions (ENCOVI) and the Sustainable Development Solutions Network, poverty trends are analyzed, key challenges are identified, and the effectiveness of government policies is described. The findings reveal a sharp rise in poverty rates, exacerbated by hyperinflation, food shortages and the collapse of public services. A lack of reliable data and government opacity make it difficult to accurately measure and track poverty. It concludes that addressing poverty in Venezuela requires a comprehensive approach that includes humanitarian assistance, economic reforms, and strengthening of social protection systems. Future research should focus on the long-term consequences of the crisis and the role of international cooperation in supporting recovery and development.